Penggunaan lembar kerja berciri representasi matematis: uji pengaruh terhadap kemampuan rekognisi simbol matematika - Zukhrufurrohmah Zukhrufurrohmah; Octavina Rizky Utami Putri (JINoP (Jurnal Inovasi Pembelajaran), 2021)
Mathematical representation is one of the mathematical recognition’s form. This study aimed to compare the ability of students' mathematical symbol recognition between learning using Student Activity Sheets characterized by mathematical representation and learning using group presentation assignment activities. The research method employed Posttest-Only Control Group Design, between the control class and the experimental class. The control class is a class with group presentation learning assignments while the experimental class is a class with learning that uses MFIs characterized by mathematical representations. The data were obtained by providing tests to measure students' mathematical recognition abilities. The data were analyzed by using the t-test. The results of calculations with the help of SPSS showed that data from both classes are normally distributed and homogeneous. The results of data analysis conducted by t-test showed sig. ≥0.05 so H1 is rejected and H0 is accepted which means that there was no difference in the ability to recognize mathematical symbols between the control class and the experimental class. There was no difference in recognition abilities between the control class and the experimental class because learning activities in both classes are student-centered learning.